Ocular Inflammatory Myofibroblastic Tumor in the Left Eye with Phthisis Right Eye: A Rare Occurrence in a Child - Sangeeta Shah; Badri Prasad Badhu; Poonam Lavaju; Anju Pradhan (Case Reports in Ophthalmological Medicine)
Inflammatory myofibroblastic tumor (IMT) is a benign pseudoneoplastic inflammatory condition with the potential for persistent local growth and recurrence that rarely affects the orbit. We report a very rare case of anterior orbital IMT in a child who presented with gradually progressive mass in left eye for 16 months. Ocular examination showed a cauliflower like exophytic mass at 360 degrees of the perilimbal area covering the entire cornea and obscuring the visualization of anterior and posterior segments. The right eye was phthisical. CT scan showed a lobulated exophytic soft tissue mass in the preseptal region and along the anterior portion of the left globe extending from medial canthus to the lateral canthus. Enucleation of the left eye was performed and the histopathological examination confirmed the diagnosis of IMT. This report aims to raise awareness about this rare ocular entity and emphasizes its early treatment as delay can result in loss of the eye.